Oil development in Lofoten : a case study of tourism and possible effects from an oil/gas development in Lofoten region - Bakos, Fredrik (Høgskolen i Bodø, 2009)
Mastergradsoppgave i Energy management - Høgskolen i Bodø, 2009 This master thesis aims to examining the aspects in which effects an oil/gas development outside Lofoten will have for the tourism industry in Lofoten. It is a focused qualitative case study of Lofoten, which investigates the effects on tourism industry of an oil/gas development outside Lofoten. A examining of Lofoten as a tourist destination and potential effects from the oil/gas development is the key words. This thesis uses stakeholder theory, in order to see what an oil/gas development outside Lofoten will have to say for the stakeholder groups. I have had a focus on tourism industry and have used impact assessment with consequence analysis as a tool to see what the oil/gas development effects will have to say for this industry and its interdependent stakeholder groups. I have also used conflict-resolving strategies to see on how the potential conflicts can be resolved. The final aspects are: 1) How will the development in Lofoten region be for the tourism industry and its interdependent stakeholders without a possible oil/gas development? 2) Sea-bottom development with onshore facilities, offshore development and oil discharge possible effects for the tourism industry, and its interdependent stakeholders. 3) How can oil companies and Norwegian government limit possible effects for the tourism industry and its interdependent stakeholders? My most interesting findings are that the population in Lofoten region is decreasing. The fishing industry is also declining and the tourism industry is getting more and more important. It is possible to get the visible impact for an oil/gas development limited (Wytch Farm example). An oil/gas development will have a time-period from 25 to 50 years (development/production). An oil discharge can have large negative impacts for the tourism industry, but the reputation can be back to normal in 5 years, but it is depended on how big the oil discharge are. There are examples of positive effects after an oil ...